Interaction of Polyamines, Abscisic Acid, Nitric Oxide, and Hydrogen Peroxide under Chilling Stress in Tomato (Lycopersicon esculentum Mill.) Seedlings - Diao, Qiannan; Song, Yongjun; Shi, Dongmei; Qi, Hongyan (Frontiers in Plant Science, 2017)
Polyamines (PAs) play a vital role in the responses of higher plants to abiotic stresses. However, only a limited number of studies have examined the interplay between PAs and signal molecules. The aim of this study was to elucidate the cross-talk among PAs, abscisic acid (ABA), nitric oxide (NO), and hydrogen peroxide (H2O2) under chilling stress conditions using tomato seedlings [(Lycopersicon esculentum Mill.) cv. Moneymaker]. The study showed that during chilling stress (4°C; 0, 12, and 24 h), the application of spermidine (Spd) and spermine (Spm) elevated NO and H2O2 levels, enhanced nitrite reductase (NR), nitric oxide synthase (NOS)-like, and polyamine oxidase activities, and upregulated LeNR relative expression, but did not influence LeNOS1 expression. In contrast, putrescine (Put) treatment had no obvious impact. During the recovery period (25/15°C, 10 h), the above-mentioned parameters induced by the application of PAs were restored to their control levels. Seedlings pretreated with sodium nitroprusside (SNP, an NO donor) showed elevated Put and Spd levels throughout the treatment period, consistent with increased expression in leaves of genes encoding arginine decarboxylase (LeADC. LeADC1), ornithine decarboxylase (LeODC), and Spd synthase (LeSPDS) expressions in tomato leaves throughout the treatment period. Under chilling stress, the Put content increased first, followed by a rise in the Spd content. Exogenously applied SNP did not increase the expression of genes encoding S-adenosylmethionine decarboxylase (LeSAMDC) and Spm synthase (LeSPMS), consistent with the observation that Spm levels remained constant under chilling stress and during the recovery period. In contrast, exogenous Put significantly increased the ABA content and the 9-cis-epoxycarotenoid dioxygenase (LeNCED1) transcript level. Treatment with ABA could alleviate the electrolyte leakage (EL) induced by D-Arg (an inhibitor of Put). Taken together, it is concluded that, under chilling stress, Spd and Spm enhanced the production of NO in tomato seedlings through an H2O2-dependent mechanism, via the NR and NOS-like pathways. ABA is involved in Put-induced tolerance to chilling stress, and NO could increase the content of Put and Spd under chilling stress.